Evaluasi Kualitas Laporan Keuangan pada Usaha Bengkel Mobil di Arda Jaya Diesel - Hafidah Muchlis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to assess the quality of financial reporting at the Arda Jaya Diesel car repair shop on Jalan Dg Hayo Antang 3. The data used are numerical data or quantitative methods. The study was conducted by collecting data from the repair shop's financial reports, such as revenue, expenses, debt, inventory, and fixed assets. The assessment was carried out by examining whether the repair shop has followed accounting principles, how to record transactions, and whether the profit and loss statements and balance sheets are accurate and reliable. The method used is a case study supported by interviews and direct observations at the repair shop. The results show that many repair shops still record their finances simply and do not follow proper accounting standards. Therefore, financial reports need to be improved to assist business decision-making and meet the reporting needs of external parties such as creditors and investors.